EXTERNAL QUALITY EVALUATION OF NON-UNIVERSITY STUDY PROGRAMMES IN LITHUANIA - Gintaute Zibeniene. (The Journal of Quality in Education, 2017)
The author analyzes the international nature of study programme evaluation with regard to the assurance of study quality. The organisation of the evaluation process of the non-university study programmes which were developed and submitted for realisation in Lithuania and other countries is also presented and compared. It is being analysed whether it is possible to identify the quality of these programmes based on quantitative and qualitative indicators.